Iryna Ivakhnenko. Activities of Vasyl Danylevych (1918 – 1936) - Ivakhnenko, Iryna (Young Scholars Grinchenko – Seton International Journal, 2022)
The article examines the multifaceted activities of Ukrainian historian, archaeologist, scholar, pedagogue, and public figure Vasyl Danylevych from 1918 to 1936. He was one of the brightest representatives of the Scientific School of Historians of Ukrainian Studies of Professor Volodymyr Antonovych at the St. Volodymyr University in Kyiv. Vasyl Danylevych returned to Ukraine in 1918 and expressed a desire to work for the benefit of the Ukrainian people and Ukrainian historical science. He worked from 1918 to 1920 as a Professor at the Kyiv State Ukrainian University, which was founded by Hetman Pavlo Skoropadsky. He taught from 1920 to 1931 at the Dragomanov Kyiv Higher Institute of Public Education. His lecture courses were devoted to Ancient Ukrainian History and Historiography. Vasyl Danylevych, from 1924, as a member of the All-Ukrainian Archaeological Committee of the Higher School of Economics and a full member of the History of Ukraine Research Department of Mykhailo Hrushevsky, headed the subsection of the History of Material Culture. His scientific interests covered a wide range of issues of History and Archeology of Kyivan Rus’, the History of Governance in Slobidska Ukraine in the 17th – 18th centuries, issues of Numismatics, Museum Studies, Historical Geography, etc. Vasyl Danylevych proved himself in various fields of science and teaching during more than 40 years of scientific and more than 30 years of teaching activities.